2016 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2016
DOI: 10.1109/iros.2016.7759527
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of a variable autonomy framework for controlling a remotely operating mobile robot

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 27 publications
8
65
0
Order By: Relevance
“…Most similar to our work, Choiu et al [5] perform a virtual experiment where subjects navigate a mobile robot through an obstacle course while noise is added at a specific section of the map. The users operate in three modes (1) full teleoperation (2) goal selection and (3) manual switching between goal selection and full teleoperation.…”
Section: Related Workmentioning
confidence: 96%
“…Most similar to our work, Choiu et al [5] perform a virtual experiment where subjects navigate a mobile robot through an obstacle course while noise is added at a specific section of the map. The users operate in three modes (1) full teleoperation (2) goal selection and (3) manual switching between goal selection and full teleoperation.…”
Section: Related Workmentioning
confidence: 96%
“…UUV operation is not a binary choice between fully manual or fully autonomous, rather there are different levels of autonomy (LoA) [35]. For this work, we will adopt and adapt the six levels of autonomy proposed for surgical robots in [36].…”
Section: Missionsmentioning
confidence: 99%
“…Operator's initiated LOA switches are based on their judgment. Previous work [3], [11] showed that humans are able to determine when they need to change LOA in order to improve performance. AI initiated LOA switches are based on a fuzzy inference engine.…”
Section: Expert-guided Mixed-initiative Control With Cognitive Availability Inferencementioning
confidence: 99%
“…The advantage of such HRS lies in the complementing capabilities of humans and Artificial Intelligence (AI). In a VA system control can be traded between a human operator and a robot by switching between different Levels of Autonomy [3], e.g. the robot can navigate autonomously while the operator is multitasking.…”
Section: Introductionmentioning
confidence: 99%